2014
DOI: 10.1002/ange.201401070
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and Modular Synthesis of New Structurally Diverse Functionalized [n]Paracyclophanes by a Ring‐Distortion Strategy

Abstract: With the goal of synthesizing new [n]paracyclophanes, the expansion of the scope of a strategy originally disclosed by Winterfeldt et al., was investigated. This approach involves sequential Diels-Alder/retro-Diels-Alder reactions, the applications of which have been constrained so far to steroid derivatives. An efficient access to new functionalized [9]-, [10]-, and [16]paracyclophanes, including original cage architectures, was developed from readily available building blocks using thermal electrocyclization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…A library of p-cyclophanes was constructed using the Diels-Alder / retro Diels-Alder approach pioneered by Winterfeldt applied to an expanded set of non-steroidal polycyclic dienes (Figure 39). 153 (Figure 40). 154 The researchers constructed an α-halo hydroxamate ester tethered by a linker to a furan unit (40-1), which could undergo base-mediated intramolecular [4+3] cycloaddition to form bridged polycycle 40-3.…”
Section: Figure 38 Sequential Diels-alder / Oxidative Ring Cleavage mentioning
confidence: 99%
See 1 more Smart Citation
“…A library of p-cyclophanes was constructed using the Diels-Alder / retro Diels-Alder approach pioneered by Winterfeldt applied to an expanded set of non-steroidal polycyclic dienes (Figure 39). 153 (Figure 40). 154 The researchers constructed an α-halo hydroxamate ester tethered by a linker to a furan unit (40-1), which could undergo base-mediated intramolecular [4+3] cycloaddition to form bridged polycycle 40-3.…”
Section: Figure 38 Sequential Diels-alder / Oxidative Ring Cleavage mentioning
confidence: 99%
“…A library of p-cyclophanes was constructed using the Diels− Alder/retro Diels−Alder approach pioneered by Winterfeldt applied to an expanded set of nonsteroidal polycyclic dienes (Figure 39). 153 Krieger et al elegantly demonstrated the construction of a set of 1,3-diene-containing substrates 39-2 via 6π electrocyclization of triene precursors 39-1. Intra-or intermolecular Diels−Alder cycloadditions with an ynoate partner formed the requisite bridging cyclohexadiene skeleton 39-3, which upon microwave heating underwent retro Diels− Alder to afford [9]-, [10]-, and [16]-p-cyclophane products 39-4.…”
Section: Chemical Reviewsmentioning
confidence: 99%